Assessment of IL-6 , IL-23 and Serum amylase Levels in Patients with Enteric Fevers - Khalil Ismail A. Mohammed; Wifaq M. Ali Al-Wattar; Suha A. Al-Fukhar; Saad Hasan Mohammed Ali; Jinan M. Mousa (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study was carried out during the period of March 2019-January 2020 for the detection of Salmonellosis in102 suspected patients with age group ranged from 17 - 69 years, who attended Baghdad teaching hospitals,that had been examined and defined as suspected cases by a specialized physician with the recording ofclinical manifestation. The diagnosis is done by the immunochromatography method, a blood sample wastaken from each patient as well as other 30 healthy control matching in age and gender. The study includedmeasurement of the level of interleukin -6,23 and Amylase activity in sera of patients and healthy control.The result indicated that anti –salmonella IgM positive in 54 cases, anti- salmonella IgG positive in 50cases, and 18 positive cases with both IgM and IgG. The Level of interleukin 6,23 increased significantlywhile the serum amylase activity decreased significantly in patients sera in comparison with healthy control.